Work incentives?: ex post effects of unemployment insurance sanctions ; evidence from West Germany - Barbara Hofmann (Center for Economic Studies and ifo Institute (CESifo), 2008)
Unemployment insurance (UI) sanctions in the form of benefit reductions are intended to set disincentives for UI recipients to stay unemployed. Empirical evidence about the effects of UI sanctions in Germany is sparse. Using administrative data we investigate the effects of sanctions on the reemployment probability in West Germany for individuals who entered UI receipt between April 2000 and March 2001. By applying a matching approach that takes timing of events into account, we identify the ex post effect of UI sanctions. As a robustness check a difference-in-differences matching estimator is applied. The results indicate positive effects on the employment probability in regular employment for both women and men.
Keywords: J64; J65; J68; 330; Unemployment insurance sanctions; dynamic matching; Arbeitslosenversicherung; Rechtsdurchsetzung; Arbeitslosigkeit; Arbeitsangebot; Ökonomischer Anreiz; Berufliche Integration; Deutschland; Alte Bundesländer